Effects of age, speech rate, and type of test on temporal auditory processing. - Vaughan NE; Letowski T (Journal of Speech, Language & Hearing Research, 1997)
Cognitive slowing that accompanies aging may be reflected in temporal aspects of auditory processing. The purpose of this study was to investigate the effects of age, type of test, and rate of speech on temporal auditory processing. Listeners were divided into three groups: young (25- to 35-year-olds), middle aged (45- to 55-year-olds), and older (65- to 75-year-olds). A method of time compression known as Synchronized Overlap Add (SOLA) was used to increase the rate of speech. This method provides a high-quality speech signal and limits the distortions that may confound the temporal effects on time-compressed tests of speech intelligibility. Listeners performed four speech understanding tasks: sentence repetition, sentence intelligibility rating, connected discourse intelligibility rating, and connected discourse comprehension question and answers at three timecompression rates (60%, 70%, and 80%). Although the older group performed more poorly on all tests, only the connected discourse intelligibility rating test was sensitive to age differences among all three groups. This difference did not appear to increase with rate increases but was present only at the 70% compression rate. In addition, variability was especially high in the oldest group of participants.